Childhood body mass index and blood pressure in prediction of subclinical vascular damage in adulthood: Beijing blood pressure cohort. Issue 1 (January 2017) - Yan, Yinkun; Hou, Dongqing; Liu, Junting; Zhao, Xiaoyuan; Cheng, Hong; Xi, Bo; Mi, Jie
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Atherosclerosis and arterial stiffness predict cardiovascular morbidity and mortality. We aimed to investigate the influence of BMI and blood pressure (BP) in childhood, and change in BMI and BP, on the development of subclinical atherosclerosis and arterial stiffness in adulthood. Methods: The study consisted of 1252 individuals aged 27–42 years who had 2–10 measurements of BMI and BP from childhood. In the final survey (2010–2011), subclinical markers of vascular damage, including carotid intima–media thickness (cIMT), carotid-femoral pulse wave velocity (cfPWV), and brachial-ankle pulse wave velocity (baPWV), were measured. Results: Pearson correlation analyses showed that BMI and BP in childhood and adulthood, and also cumulative and incremental values from childhood to adulthood, were all significantly associated with adult cIMT, cfPWV, and baPWV in males and in females (all P  < 0.05). In the multivariate logistical analyses, for both sexes, childhood BMI and systolic BP (SBP) predicted high cIMT in adulthood, and childhood SBP predicted high cfPWV and high baPWV in adulthood. However, these associations were largely attenuated and became nonsignificant after additional adjustment for adult BMI and SBP, except that childhood SBP showed a borderline significant association with high cfPWV in adulthood for males. In addition, for both sexes, incremental BMI and SBP from childhood to adulthood predicted high cIMT in adulthood, and incremental SBP predicted high cfPWV and high baPWV in adulthood, independent of childhood values. Conclusion: The adverse influence of high BMI and high BP on subclinical vascular damage begins in childhood. This study enhances the importance of early prevention and lifelong treatment of excessive weight and elevated BP.